Studies on the Fusarium stalk rot infection of the maize genotypes using the Findex percentage and a computerised image analysis program - Szőke, Csaba; Virág, István; Magyar, Donát; Rácz, Ferenc; Marton, Csaba L. (Acta Agraria Debreceniensis, 2011)
In a continental climate, the pathogens causing the most serious problems are species belonging to the Fusarium genus. When the pathogen attacks the stalk, the plant dies earlier, reducing grain filling and resulting in small, light ears. In addition, the stalks break or lodge, resulting in further yield losses from ears that cannot be harvested. During the three years of the experiment, 14 inbred lines were examined. The genotypes were sown in a two-factor split-plot design with four replications, with the genotypes in the main plots and four treatments in the subplots: two Fusarium graminearum isolates (1. FG36, 2. FGH4), 3. sterile kernels, 4. untreated control. The results experiments showed significant differences between the genotypes for resistance to fusarium stalk rot. Among the inbred lines the best resistance to fusarium stalk rot was exhibited by P06 and P07, both of which were related to ISSS. The precision and sensitivity of disease evaluations carried out visually and using image analysis software were compared in the experiment, and with two exceptions the CV values were lower for the image analysis. As the CV for measurements can be considered as a relative error, it can be stated that image analysis is the more precise of the two methods, so this technique gives a more accurate picture of the extent of stalk rot. The extent of stalk rot developing in response to natural infection is extremely environment-dependent, so the use of artificial inoculation is recommended for selection trials.